PENGEMBANGAN MODUL PIL (PHYSICS, I’M IN LOVE) BERBASIS EKSPERIMEN SEDERHANA - Yahya, Tengku Novenia; Nasir, Muhammad; ', Syahril (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The aim of this research was to produce module PIL (Physics, I’m in Love) based on simple experiment on material of light and optical was valid and suitable for use as a supplement Physics learning media for students. This research type using Research and Development (R&D) method with a model of the development was Four-D Model. The module was developed through four phases according to the development model being used such as Define, Design, Develop and Dessiminates phase. The research data was obtained from the results of validation by three experts as validators. Instrument validation using content validity to assessment module by Badan Standar Nasional Pendidikan (BSNP) which consists of four feasibility aspects’s modules with 56 indicators assessment module and questionnaires adaptation about three strategies PIL. Validation was done through two phases which is validation in first phase and validation in second phase. The results of the validation first phase got an average value of 3.88 and the validation second phase got an average value 4.04. Both of the phase produce quality module to the category of